To catch a firefly / Emmy Sanders. - Sanders, Emmy (Emmy Sanders, 2024)
There's a lot I've never told my best friend. The fact that I love him. That I miss him every day he's gone. That, sometimes, I ache for him with a ferocity that leaves me breathless. Lucky Buchanan tore into my life as a boy, wild and daring, my opposite in every way. He drew me in, stole my heart without trying. He hears me, even though I rarely speak a word. But I always knew this place wouldn't be enough for my free-spirited friend. I knew he wasn't mine to keep. So why, when I finally try to get over him, does he sweep back into town? Why is he upset? Why is there tension between us for the first time in years? I never saw a future where Lucky could be mine. But now, unless I want to lose my friend, I might not have a choice but to tell the truth. My heart belongs to him. It has from the start. If only I knew how to hold onto a creature that's meant to fly.